Corporate Governance in Listed Companies - Erwin Harinurdin; Karin Amelia Safitri (Jurnal Vokasi Indonesia, 2022)
The purpose of this study is to examine and analyze the implementation of the principles of Good Corporate Governance (GCG) in publicly listed companies on the IDX and the obstacles faced in its implementation. The indicators for GCG principles are fairness, transparency, accountability, and responsibility. This study uses a sample of companies listed on the Indonesia Stock Exchange (IDX) with the criteria of having published an annual report and a 2018 publication date is available. This study uses a corporate governance index. This research is a descriptive research using qualitative analysis. This study found a fairly good increase every year since the implementation of GCG, not just compliance with rules and regulations, but also a strong commitment and make it a corporate culture. The constraints faced by go public companies are not impossible to fulfill in the future. The process of transforming change from power into checks and balances involving all elements within the company is not an easy process, but it must continue to be observed and challenged by the company and make continuous improvements in the future.